Quality of life of patients with spinal muscular atrophy: A systematic review. (May 2019) - Landfeldt, Erik; Edström, Josefin; Sejersen, Thomas; Tulinius, Már; Lochmüller, Hanns; Kirschner, Janbernd
Abstract: Objectives: To systematically review the literature of quality of life (QoL) of patients with spinal muscular atrophy (SMA), a rare, autosomal-recessive neuromuscular disease associated with extensive morbidity and elevated mortality. Methods: We searched Embase, Web of Science, and PubMed for full-text, English-language articles (published between January 1, 2000 and July 31, 2018) reporting results from studies of QoL of patients with SMA. We excluded review and editorial articles, studies reporting results for samples comprising <5 patients (to allow for meaningful inference), and case reports/qualitative assessments. Results: Of 824 identified articles, 15 met study criteria. Included publications contained data derived from samples from a total of 11 countries and three continents (Europe, North America, and South America). Estimates of the latent trait, primarily derived using the Pediatric Quality of Life Inventory (PedsQL) 4.0 Generic Core Scales and the PedsQL 3.0 Neuromuscular Module, indicated impairment in patient QoL, in particular physical functioning. However, both patient self- and caregiver proxy-assessments varied markedly across studies and subgroups. Among adult individuals, the mean self-assessed EuroQol-5D-3L utility has been estimated at 0.16 for a pooled sample of patients with SMA type I, II, and III, and −0.01 for SMA type II. Little is known of the impact of available treatments, including nusinersen, on patient QoL. Conclusions: Our review show that QoL is impaired in SMA, mainly due to compromised physical health, but also reveal that little is known of the impact of the disease across different phenotypes and clinical interventions. Highlights: Quality of life (QoL) is impaired in patients with spinal muscular atrophy (SMA). SMA appears to primarily impact physical domains of QoL. Yet, estimates of QoL in SMA vary markedly across study populations and phenotypes. Little is known regarding how QoL in SMA is modified by available treatments.